(untitled) (AYUSHDHARA, 2019)
In our classical texts, we find that Shodhan is defined as a process through which we attempt to remove impurities that may be present in any material of herbal or mineral origin. Haratal has been placed among the Uprasavarga, & along with Manashila & Sankhiya forms the Mallavarga. All these are highly toxic unless Shodhan is done. Haratal shodhan in our texts has been mentioned by subjecting it to Swedana in Dola yantra. The liquid medium being any, from the following i.e. Kushmandaswarasa, Churnodak, Triphalakwathnimbuswarasa etc., with the duration ranging from 1-2 Prahar (3 to 6 hrs). In the following study, Ashudha haratal was subjected to Swedana in Churnodaka for 2 Prahar, i.e., for 6 hr. Samples were collected of Ashudha haratal, Shudha haratal, and the Churnodaka left after completion of Swedan. XRF analysis of Shudha and Ashudha haratal show that elements like iron were completely removed or in case of antimony and silicon reduction, was noted. While traces of elements like iron, arsenic etc were noted in the XRF analysis of the Churnodaka that was collected after the Shodhan procedure. Since Haratal can be used in medicine/formulation after its purification, the current study has been undertaken to study the process of its purification (Shodhan).